2012
DOI: 10.1093/icvts/ivs340
|View full text |Cite
|
Sign up to set email alerts
|

Thymic haemangioma presenting with a left innominate vein aneurysm: insight into the aetiology

Abstract: Thymic haemangiomas and innominate vein aneurysms are rare with only 7 and 19 previous cases, respectively, reported in the medical literature. The aetiology of an innominate vein aneurysm remains unclear and there is no previous report of tumour involvement. We present the case of a 27-year old male with concomitant mediastinal tumour and innominate vein aneurysm who underwent surgical treatment. The tumour intruded into the lower section of the innominate vein, thus causing aneurysmal dilation. Pathologicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…Aneurysms may also occur secondary to arteriovenous fistulae [2,6]. We previously reported that a thymic cavernous hemangioma may be included in the etiology of an innominate vein aneurysm because the tumor may retract the lower portion of the left innominate vein [2]. Compared with our previous case, which had a convex-shaped left innominate vein aneurysm, our current case had a fusiform-shaped left innominate vein aneurysm.…”
Section: Commentmentioning
confidence: 51%
See 4 more Smart Citations
“…Aneurysms may also occur secondary to arteriovenous fistulae [2,6]. We previously reported that a thymic cavernous hemangioma may be included in the etiology of an innominate vein aneurysm because the tumor may retract the lower portion of the left innominate vein [2]. Compared with our previous case, which had a convex-shaped left innominate vein aneurysm, our current case had a fusiform-shaped left innominate vein aneurysm.…”
Section: Commentmentioning
confidence: 51%
“…Furthermore, a coexisting left innominate vein aneurysm was discovered. Innominate vein aneurysms are also rare, with only 20 cases reported to date [2]. Therefore, a thymic cavernous hemangioma with a left-side innominate vein aneurysm, as in our case, is very rare.…”
mentioning
confidence: 59%
See 3 more Smart Citations